Orthopedic surgical robotic systems in knee arthroplasty: a comprehensive review - Fan, Xuanze; Wang, Yan; Zhang, Shouwei; Xing, Yuan; Li, Jinhua; Ma, Xinlong; Ma, Jianxiong (Frontiers in Bioengineering and Biotechnology, 2025)
In conjunction with the accelerated evolution of robotics, the advancement of robot-assisted minimally invasive surgical systems is occurring at a similarly accelerated pace, and is becoming increasingly accepted. It is employed in numerous surgical specialties, including orthopedics, and has significantly transformed traditional surgical techniques. Among these applications, knee arthroplasty represents one of the most prevalent and efficacious procedures within the domain of robot-assisted orthopedic surgery. The implementation of surgical robotic systems has the potential to enhance the precision and accuracy of surgical outcomes, facilitate reproducibility, reduce technical variability, mitigate patient discomfort, and accelerate recovery. In this paper, a literature review of the Web of Science and PubMed databases was conducted to search for all articles on orthopedic surgical robotics through November 2024. It mainly summarizes the most commonly used and widely accepted robotic systems in the field of orthopedic surgery, with a particular focus on their application in knee arthroplasty procedures. Orthopedic robotic systems can be classified into three principal categories: autonomous robotic systems, semi-autonomous robotic systems, and teleoperated robotic systems. In the context of knee arthroplasty, the characteristics of different robotic systems are examined in relation to three types of Total Knee Arthroplasty (TKA), Unicompartmental Knee Arthroplasty (UKA) and Patellofemoral Arthroplasty (PFA). In conclusion, the current state of orthopedic surgical robotics is reviewed, and future development prospects and challenges are proposed.